Kulkeeko Suomi taas jälkijunassa? Brigit Toebes – Mette Hartlev – Aart Hendriks – Katharina Ò Cathaoir – Janne Rothmar Herrmann – Henriette Sinding Aasen: Health and Human Rights. Global and European Perspectives. 2nd Edition. Cambridge: Intersentia 2022. - Nieminen, Liisa (Lakimies, 2025)